2002
DOI: 10.1002/cne.10274
|View full text |Cite
|
Sign up to set email alerts
|

Sensory neuron addition in juvenile rat: Time course and specificity

Abstract: The time course and specificity of neuron addition to lumbar dorsal root ganglia (DRGs) L(4)-L(6) of rats was investigated. By using methods validated by three-dimensional reconstructions, profile counts in paraffin sections of nucleoli within a nucleus were 36% greater in 100-day-old (P100) rats than in 1-day-old (P1) rats. Adult values were reached by P50. Added neurons fell disproportionately into the population of neurons whose size was below that of the mean size within the ganglion. The biochemical chara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0
1

Year Published

2002
2002
2016
2016

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 48 publications
1
24
0
1
Order By: Relevance
“…This finding supports and extends previous studies in frog and rat DRGs (St Wecker and Farel, 1994;Meeker and Farel, 1997;Popken and Farel, 1997;Farel, 2002Farel, , 2003, which signaled differences between sensory ganglia and well defined neurogenic regions in CNS in which the birth of new neurons is the main strategy for the increase, or maintenance, of neuron numbers. Protracted differentiation could thus be a developmental strategy that confers an adaptive advantage to neural populations that need to respond to changes in their environment by adding or renewing neurons without the prerequisite of DNA synthesis or cell-cycle reentry.…”
Section: Overview and Future Directionssupporting
confidence: 91%
See 2 more Smart Citations
“…This finding supports and extends previous studies in frog and rat DRGs (St Wecker and Farel, 1994;Meeker and Farel, 1997;Popken and Farel, 1997;Farel, 2002Farel, , 2003, which signaled differences between sensory ganglia and well defined neurogenic regions in CNS in which the birth of new neurons is the main strategy for the increase, or maintenance, of neuron numbers. Protracted differentiation could thus be a developmental strategy that confers an adaptive advantage to neural populations that need to respond to changes in their environment by adding or renewing neurons without the prerequisite of DNA synthesis or cell-cycle reentry.…”
Section: Overview and Future Directionssupporting
confidence: 91%
“…Recent stereological studies have confirmed the fact of neuron addition in adult rat DRG (Cecchini et al, 1993(Cecchini et al, , 1994(Cecchini et al, , 1995Popken and Farel, 1997;Ciaroni et al, 2000;Farel, 2002).…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…Others have reported morphometric evidence for the formation of new neurons in postnatal or adult rat DRG as a normal process of development Popken and Farel, 1997;Farel, 2002;Guena et al, 2002). In a previous study using oral BrdU administration via drinking water for 1 month after sciatic transection, we found only a handful of BrdUlabeled ipsilateral DRG neurons after 2 months (Groves et al, 2003).…”
Section: Neurogenesis In Adult or Postnatal Dorsal Root Gangliamentioning
confidence: 86%
“…To determine the accuracy of profile counts in frozen material, sets of three consecutive 8-m sections that had been immunoreacted for Substance P (SP) were selected from the middle third of DRG L 4 of each of four P5 and four P100 rats (Farel, 2002). Digital images were captured, printed, and assembled into collages at a final magnification of 400ϫ.…”
Section: Studies In the Ratmentioning
confidence: 99%